Here
"P=4x-\\dfrac{1}{x},"
"Q=4x^2"
"R=2x^2"
Changing the independent variable from "x" to "z"
where
"Q_1=\\dfrac{Q}{({dz\\over dx})^2}"
"R_1=\\dfrac{R}{({dz\\over dx})^2}"
We choose "z" such that
Let
Then
Integrating
"z=x^2"We have
"P_1=\\dfrac{{d^2z\\over dx^2}+P{dz\\over dx}}{({dz\\over dx})^2}=\\dfrac{2+(4x-\\dfrac{1}{x})(2x)}{(2x)^2}=2"
"R_1=\\dfrac{R}{({dz\\over dx})^2}=\\dfrac{2x^2}{(2x)^2}={1\\over 2}"
"{d^2y\\over dz^2}+2{dy\\over dz}+y={1\\over 2}"
Method of undetermined coefficients
Homogeneous second order differentional equation
Characteristic equation
The general solution of the homogeneous differential equation is
Let "Y=A," then
"Y={1\\over 2}"
The general solution of the nonhomogeneous equation
"y(z)=C_1ze^{-z}+C_2e^{-z}+{1\\over 2}"
Substitute "z=x^2" and obtain the general solution
Comments
Leave a comment